Gestão e gerenciamento de recursos hídricos no estado de Mato Grosso - Batista, Victória Gabriela da Paz (2022)
Water is an essential resource for life, however, it is limited, and conflicts due to its scarcity are already observed in several regions of the planet. The present work aims to present a general scenario of the management and management of water resources in Brazil, especially in the State of Mato Grosso. The main characteristics of the State's water resources and the legal aspects related to the subject are presented, addressing the institutional changes that occurred due to the implementation of the new State Policy on Water Resources, established by Law No. 11.088/2020. A hierarchical arrangement for the State Water Resources System is presented, based on its structure, competences and articulation, and presents a proposal for an arrangement of entities for the execution of the instruments of the State Water Resources Policy of Mato Grosso. It is concluded that there has been progress in updating the State Policy on Water Resources, with the inclusion and strengthening of entities and instruments, however, it is clear that Mato Grosso still needs to evolve and consolidate them for their implementation.